The Cleavage Model, Ethnicity and Voter Alignment in Africa: Conceptual and Methodological Problems Revisited - Gero Erdmann (German Institute of Global and Area Studies (GIGA), 2007)
Recent research on political parties and ethnicity has challenged the conventional wisdom about ethnicity as the major factor that explains voter alignment in Africa. The paper maintains that the cleavage model, although modified to include ethnicity, still provides heuristically the best foundation for the explanation of party formation and voting behaviour in Africa. It points out that inconclusive and contradicting research results about the salience of ethnicity can be attributed to a variety of unresolved methodological and conceptual problems linked to the 'fluidity' of the concept of ethnicity. To overcome these problems refined research designs and more sophisticated analytical tools are required. Finally, it is safe to assume that the relevance of ethnicity for the formation of party systems and voter alignment is not a uniform pattern across Africa, but will differ from one country to the other. – – Jüngere Forschungsergebnisse stellen Ethnizität als Erklärungsfaktor für das Wahlverhalten in Afrika (südlich der Sahara) in Frage. Der Beitrag bestätigt die These, dass der soziale Konfliktlinienansatz in heuristischer Weise und im Hinblick auf Ethnizität modifiziert auf Afrika anwendbar ist und eine maßgebliche Erklärung für die Formation von Parteiensystemen in Afrika liefern kann. Die widersprüchlichen und wenig aufschlussreichen Forschungsergebnisse zum Zusammenhang von Ethnizität und Wählerverhalten können mit einer Reihe ungelöster methodischer und konzeptioneller Schwierigkeiten erklärt werden, die mit der Fluidität des Ethnizitätsbegriffes verbunden sind. Um diese Probleme zu überwinden, sind spezifische Forschungsdesigns und ausgefeiltere Analyseinstrumente notwendig. Grundsätzlich lässt sich mit einiger Sicherheit festhalten, dass Ethnizität für die Parteienformation und das Wählerverhalten nicht überall in Afrika gleichermaßen relevant ist, sondern sich ihre Bedeutung von Land zu Land erheblich unterscheiden kann.
Keywords: 300; Africa; social cleavages; cleavage model; ethnicity; political parties; party systems